2014
DOI: 10.1080/17512549.2013.865552
|View full text |Cite
|
Sign up to set email alerts
|

Identification of elements to control and regulate residential energy consumption

Abstract: Residential energy consumption in the USA has been marked by a steady growth over the past decades in spite of the implementation of various energy efficiency policies. To develop effective energy efficiency policies for the residential sector, it is important to understand the causal factors and their effects on residential energy consumption. There is a dearth of literature on plausible ways to modify and manipulate factors that influence residential energy consumption. This paper builds on previous study by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…In addition to policy, environmental, and technical issues, many research topics identify factors affecting household energy consumption [28][29][30] and behavioral intervention [31][32][33].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to policy, environmental, and technical issues, many research topics identify factors affecting household energy consumption [28][29][30] and behavioral intervention [31][32][33].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Effective demand-side management strategy design for the residential sector depends on proper identification of factors that are responsible for driving electricity demand at houses. A large and growing body of literature has investigated different household factors such as building characteristics, socio-demographic characteristics and found relationship in driving residential electricity demand [115][116][117][118][119][120][121]. For example, Brounen et al (2012) found that electricity consumption at houses varies predominantly due to family composition and income of the household [117].…”
Section: Factors Responsible For Residential Demandmentioning
confidence: 99%
“…Such analysis concerning human dimensions and built environments is well established in the literature and covers a wide spectrum of categories, specifically demographic and socioeconomic factors. Bhattacharjee et al [13] found correlations between residential energy consumption and consumer attitude, along with demographics, economy, and climate that can, in turn, be attributed to intervention strategies. Authors in Ref.…”
Section: Introductionmentioning
confidence: 99%